Hubungan Kebiasaan Sarapan Terhadap Pemenuhan Aktivitas Fisik dan Konsentrasi Belajar Siswa Sekolah Dasar di SDN Mangun Jaya 04 Tambun Selatan - Stri Elsa Sabitsa; Guntari Prasetya (Jurnal Ilmiah Wahana Pendidikan, 2023)
Breakfast habits is a routine eating activity in the morning to meet energy needs in order to carry out activities optimally and support learning concentration. This study is aimed to analyze the relationship between breakfast habits and the provision of physical activity and learning concentration in elementary school students at SDN Mangun Jaya 04 Tambun Selatan. This research is a quantitative research with a cross sectional design. The number of samples was 79 students at SDN Mangun Jaya 04 Tambun Selatan, which were selected by simple random sampling method. Data collection were taken by using self-administered questionnaires covering aspects of breakfast habits, physical activity (PAQ-C), and learning concentration. Data were analyzed by using Chi Square test. The results showed that there were a significant relationship between breakfast habits and physical activity, as well as breakfast habits and learning concentration in elementary school students at SDN Mangun Jaya 04 Tambun Selatan (p-value <0,05). In conclusion, there were a relationship between breakfast habits and the provision of physical activity and learning concentration of elementary school students at SDN Mangun Jaya 04 Tambun Selatan.